Characterization of the differences in strength and power between different levels of competition in Rugby Union athletes - Argus, C. K.; Gill, N. D.; Keogh, J. W. L. (The Journal of Strength and Conditioning Research, 2012)
Levels of strength and power have been used to effectively discriminate between different levels of competition; however, there is limited literature in rugby union athletes. To assess the difference in strength and power between levels of competition, 112 rugby union players, including 43 professionals, 19 semiprofessionals, 32 academy level, and 18 high school level athletes, were assessed for bench press and box squat strength, and bench throw, and jump squat power. High school athletes were not assessed for jump squat power. Raw data along with data normalized to body mass with a derived power exponent were log transformed and analyzed. With the exception of box squat and bench press strength between professional and semiprofessional athletes, higher level athletes produced greater absolute and relative strength and power outputs than did lower level athletes (4-51%; small to very large effect sizes). Lower level athletes should strive to attain greater levels of strength and power in an attempt to reach or to be physically prepared for the next level of competition. Furthermore, the ability to produce high levels of power, rather than strength, may be a better determinate of playing ability between professional and semiprofessional athletes.